PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA PEGAWAI DINAS KEBERSIHAN DAN PERTAMANAN KABUPATEN PESAWARAN - Miswan Gumanti; Bernadhita Herindri Samodera Utami (STIE Trisna Negara OKU Timur, 2019)
The purpose of this study was to determine the effect of motivation and discipline on the performance of the Sanitation and Landscaping Service staff of Pesawaran District. Variable measurements using a questionnaire distributed to employees of the Cleaning and Gardening Office of Pesawaran District. Analysis using statistics and the results of the questionnaire statement are valid and reliable. The sampling technique used was a saturated sample with a population of 114 samples. Then the normality test and path analysis were carried out. The path analysis results prove that the motivation and discipline variables simultaneously which directly affect the performance of the Sanitation and Landscaping Department of Pesawaran District are 52.5% and the remaining 47.5% is influenced by other factors not explained in this study. Motivation that directly affects the performance of the Sanitation and Landscaping Service Office of Pesawaran District is 39.2% and the discipline directly affects the performance of the Sanitation and Landscaping Service Office of Pesawaran District by 41.1%..